ANALISIS KOMPETENSI WIDYAISWARA PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI SULAWESI TENGGARA - Amalul Syahid (Journal Publicuho, 2021)
This study aims to analyze the competence of Widyaiswara at the Human Resources Development Agency (BPSDM) Prov. Southeast Sulawesi. Survey research method, research time in December 2021. The population of this research is Widyaiswara (WI) at BPSDM Prov. Southeast Sulawesi, totaling 12 people. Because the number of population is small, the sampling is total sampling, that is, the entire population is the sample. Data collection using a questionnaire. Measurement scale, Likert scale. Univariate data analysis, using SPSS program. The results of this study indicate that there is no WI that has patented innovation inventions or Intellectual Property Rights (IPR). Most of the respondents (41.7%, n=5) did not have any scientific publications. There are 3 respondents (25%) who have only attended training/TOT once in the last 3 years, and 83.3% (n=10) of respondents have not made a scientific oration. This shows the competence of Widyaiswara at BPSDM Prov. Southeast Sulawesi still needs to be improved, including in terms of competence in producing scientific publications in scientific journals, newspapers and through scientific orations.